Review of the rehabilitation process of 13 to 16 year old youths in conflict with the law, assessed at the Macassar arrest, assessment and referral centre - De Bruyn, Dianne Juanita (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2004.